The effect of using the Flipped Learning strategy on the academic achievement of sixth grade students and their attitudes towards learning geography - Al- Edamat, Ghaleb Hussein (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed to identify the effect of using the flipped Learning strategy on the academic achievement of sixth graders and their attitudes towards learning geography in Jordan. The study sample consists of (50) students deliberately chosen from Um al- Quttein basic school for boys in the North- East district of education. The students were randomly distributed into two groups (experimental and controlling). The experimental group were taught by using the strategies of flipped learning, the controlling was taught by the ordinary method. In order to achieve the purpose of the study, the test is designed to measure the trends of sixth grade students to learn geography using the flipped learning strategy, and providing indications about the sincerity and constancy of tools, and the tools were applied to the group before and after, the study took three weeks, the study ends up with the following results: The presence of statistically significant differences at the level of significance (a=0.5) in the academic achievement of the sixth grade students to learn geography, for the benefit of the flipped learning strategy. The presence of statistically significant differences at the level of significance (α≤0.05) Trends in the sixth grade students in learning the geography, for the benefit of the flipped learning strategy. There is effective in the use of the education strategy and mirrored in the academic achievement of students. In the light of the findings of the current study, the research trained geography teachers on how to use the flipped learning modern teaching strategy for its usefulness in the level of the collection of students in the scientific article and improve their attitudes toward learning the geography of scientific material.